Empirical evidence suggests adverse climate events have not affected Australian women's health and well‐being - Jennifer R. Powers; Deborah Loxton; Jeanine Baker; Jane L. Rich; Annette J. Dobson (Elsevier, 2012)
Abstract Objective: To compare the health and well‐being of women by exposure to adverse climate events. An Exceptional Circumstance declaration (EC) was used as a proxy for adverse climate events. The Australian government may provide financial support to people living in EC areas, i.e. areas experiencing a one in 20-25 year event (drought, flood or fire) that results in a severe, extended downturn in farm or farm‐related income. Methods: Data from 6,584 53-58 year old non‐metropolitan women participating in the 2004 survey of the Australian Longitudinal Study on Women's Health (ALSWH) were linked to EC data. Generalised linear models were used to analyse differences in SF‐36 General Health (GH) and Mental Health (MH) and perceived stress by EC for all women. Models were adjusted for demographic, health‐related and psychosocial factors potentially on the pathway between EC and health. Given that the effects on health were expected to be greater in vulnerable people, analyses were repeated for women with worse socioeconomic circumstances. Results: GH, MH and stress did not differ for the 3,366 women in EC areas and 3,218 women in non‐EC areas. GH, MH and stress were worse among vulnerable women (who had difficulty managing on available income) regardless of EC. Conclusion and implications: This research adds to the existing literature on climate change, associated adverse climate events and health, by suggesting that multiple resources available in high income countries, including government support and individual psychosocial resources may mitigate some of the health impacts of adverse climate events, even among vulnerable people.